Precalculus

Trigonometry

Trigonometry Logo

Power-Reduction Formulas

Solved Problems

Click or tap a problem to see the solution.

Example 1

Find the value of cos4α given that cos 2α = 1/3.

Example 2

Calculate 2cos2(π/8) − 1.

Example 3

Write an expression for \({\sin ^2}\alpha \,{\cos ^2}\alpha \) that does not contain powers of trigonometric functions greater than \(1.\)

Example 4

Find the value of \({\tan^4}\alpha\) given that \(\cos 2\alpha = -\frac{1}{4}.\)

Example 5

Calculate \({\sin ^4}\frac{\pi }{{12}} + {\cos ^4}\frac{\pi }{{12}}.\)

Example 6

Calculate \({\tan ^5}\frac{\pi }{6}.\)

Example 7

Find the value of \({\cot ^4}\alpha\) given that \(\cos \alpha = \frac{2}{3}.\)

Example 8

Write an expression for \({\sin ^3}\alpha \,{\cos ^3}\alpha \) that does not contain powers of trigonometric functions greater than \(1.\)

Example 1.

Find the value of \({\cos ^4}\alpha\) given that \(\cos 2\alpha = \frac{1}{3}.\)

Solution.

We represent \({\cos ^4}\alpha\) as \({\left( {{{\cos }^2}\alpha } \right)^2}\) and apply the squared power reduction formula for cosine:

\[{\cos ^4}\alpha = {\left( {{{\cos }^2}\alpha } \right)^2} = {\left( {\frac{{1 + \cos 2\alpha }}{2}} \right)^2} = {\left( {\frac{{1 + \frac{1}{3}}}{2}} \right)^2} = {\left( {\frac{{\frac{4}{3}}}{2}} \right)^2} = {\left( {\frac{2}{3}} \right)^2} = \frac{4}{9}.\]

Example 2.

Calculate \(2\,{\cos ^2}\frac{\pi }{8} - 1.\)

Solution.

We will apply the squared power reduction rule for cosine. This yields:

\[2\,{\cos ^2}\frac{\pi }{8} - 1 = 2\left( {\frac{{1 + \cos \frac{\pi }{4}}}{2}} \right) - 1 = \cancel{1} + \cos \frac{\pi }{4} - \cancel{1} = \cos \frac{\pi }{4} = \frac{{\sqrt 2 }}{2}.\]

Example 3.

Write an expression for \({\sin ^2}\alpha \,{\cos ^2}\alpha \) that does not contain powers of trigonometric functions greater than \(1.\)

Solution.

Using the squared power reduction rules for sine and cosine, we have

\[{\sin ^2}\alpha \,{\cos ^2}\alpha = \frac{{1 - \cos 2\alpha }}{2} \cdot \frac{{1 + \cos 2\alpha }}{2} = \frac{{\left( {1 - \cos 2\alpha } \right)\left( {1 + \cos 2\alpha } \right)}}{4} = \frac{{1 - {{\cos }^2}2\alpha }}{4}.\]

Apply the reduction indetity for \({{{\cos }^2}2\alpha }.\) This yields:

\[{\sin ^2}\alpha \,{\cos ^2}\alpha = \frac{{1 - {{\cos }^2}2\alpha }}{4} = \frac{{1 - \frac{{1 + \cos 4\alpha }}{2}}}{4} = \frac{{\frac{{2 - 1 - \cos 4\alpha }}{2}}}{4} = \frac{{1 - \cos 4\alpha }}{8}.\]

Example 4.

Find the value of \({\tan^4}\alpha\) given that \(\cos 2\alpha = -\frac{1}{4}.\)

Solution.

We write \({\tan^4}\alpha\) as \({\left( {{{\tan }^2}\alpha } \right)^2}\) and use the following power reduction rule:

\[{\tan ^2}\alpha = \frac{{1 - \cos 2\alpha }}{{1 + \cos 2\alpha }}.\]

This gives:

\[{\tan ^4}\alpha = {\left( {{{\tan }^2}\alpha } \right)^2} = {\left( {\frac{{1 - \cos 2\alpha }}{{1 + \cos 2\alpha }}} \right)^2} = {\left( {\frac{{1 - \left( { - \frac{1}{4}} \right)}}{{1 - \frac{1}{4}}}} \right)^2} = {\left( {\frac{{\frac{5}{4}}}{{\frac{3}{4}}}} \right)^2} = {\left( {\frac{5}{3}} \right)^2} = \frac{{25}}{9}.\]

Example 5.

Calculate \({\sin ^4}\frac{\pi }{{12}} + {\cos ^4}\frac{\pi }{{12}}.\)

Solution.

Using the power reduction formulas for \({\sin ^4}\frac{\pi }{{12}}\) and \({\cos ^4}\frac{\pi }{{12}},\) we can write:

\[{\sin ^4}\frac{\pi }{{12}} = \frac{{3 - 4\cos \frac{\pi }{6} + \cos \frac{\pi }{3}}}{8},\]
\[{\cos ^4}\frac{\pi }{{12}} = \frac{{3 + 4\cos \frac{\pi }{6} + \cos \frac{\pi }{3}}}{8}.\]

Substitute this in the original expression:

\[{\sin ^4}\frac{\pi }{{12}} + {\cos ^4}\frac{\pi }{{12}} = \frac{{3 - 4\cos \frac{\pi }{6} + \cos \frac{\pi }{3}}}{8} + \frac{{3 + 4\cos \frac{\pi }{6} + \cos \frac{\pi }{3}}}{8} = \frac{{3 - \cancel{{4\cos \frac{\pi }{6}}} + \cos \frac{\pi }{3} + 3 + \cancel{{4\cos \frac{\pi }{6}}} + \cos \frac{\pi }{3}}}{8} = \frac{{6 + 2\cos \frac{\pi }{3}}}{8} = \frac{{2\left( {3 + \cos \frac{\pi }{3}} \right)}}{8} = \frac{{3 + \cos \frac{\pi }{3}}}{4} = \frac{{3 + \frac{1}{2}}}{4} = \frac{{\frac{7}{2}}}{4} = \frac{7}{8}.\]

Example 6.

Calculate \({\tan ^5}\frac{\pi }{6}.\)

Solution.

We represent \({\tan ^5}\frac{\pi }{6}\) as the product \({\tan ^2}\frac{\pi }{6}{\tan ^3}\frac{\pi }{6}.\) Then using the power reduction formulas, we obtain

\[{\tan ^5}\frac{\pi }{6} = {\tan ^2}\frac{\pi }{6}{\tan ^3}\frac{\pi }{6} = \frac{{1 - \cos \frac{\pi }{3}}}{{1 + \cos \frac{\pi }{3}}} \cdot \frac{{3\sin \frac{\pi }{6} - \sin \frac{\pi }{2}}}{{3\cos \frac{\pi }{6} + \cos \frac{\pi }{2}}} = \frac{{1 - \frac{1}{2}}}{{1 + \frac{1}{2}}} \cdot \frac{{3 \cdot \frac{1}{2} - 1}}{{3 \cdot \frac{{\sqrt 3 }}{2} + 0}} = \frac{{\frac{1}{2}}}{{\frac{3}{2}}} \cdot \frac{{\frac{1}{2}}}{{\frac{{3\sqrt 3 }}{2}}} = \frac{1}{{9\sqrt 3 }}.\]

Example 7.

Find the value of \({\cot ^4}\alpha\) given that \(\cos \alpha = \frac{2}{3}.\)

Solution.

We will use the following identity:

\[{\cot ^4}\alpha = \frac{{3 + 4\cos 2\alpha + \cos 4\alpha }}{{3 - 4\cos 2\alpha + \cos 4\alpha }}.\]

Calculate \({\cos 2\alpha }\) by the double angle formula:

\[\cos 2\alpha = 2\,{\cos ^2}\alpha - 1 = 2 \cdot {\left( {\frac{2}{3}} \right)^2} - 1 = 2 \cdot \frac{4}{9} - 1 = \frac{{8 - 9}}{9} = - \frac{1}{9}.\]

Similarly find \({\cos 4\alpha:}\)

\[\cos 4\alpha = 2{\cos ^2}2\alpha - 1 = 2 \cdot {\left( { - \frac{1}{9}} \right)^2} - 1 = 2 \cdot \frac{1}{{81}} - 1 = - \frac{{79}}{{81}}.\]

Substitute these results in the expression for \({\cot ^4}\alpha:\)

\[{\cot ^4}\alpha = \frac{{3 + 4\cos 2\alpha + \cos 4\alpha }}{{3 - 4\cos 2\alpha + \cos 4\alpha }} = \frac{{3 + 4 \cdot \left( { - \frac{1}{9}} \right) + \left( { - \frac{{79}}{{81}}} \right)}}{{3 - 4 \cdot \left( { - \frac{1}{9}} \right) + \left( { - \frac{{79}}{{81}}} \right)}} = \frac{{3 - \frac{4}{9} - \frac{{79}}{{81}}}}{{3 + \frac{4}{9} - \frac{{79}}{{81}}}} = \frac{{\frac{{243 - 36 - 79}}{{81}}}}{{\frac{{243 + 36 - 79}}{{81}}}} = \frac{{128}}{{200}} = \frac{{16}}{{25}}.\]

Example 8.

Write an expression for \({\sin ^3}\alpha \,{\cos ^3}\alpha \) that does not contain powers of trigonometric functions greater than \(1.\)

Solution.

Using the cubed power reduction rules, we can write:

\[{\sin ^3}\alpha \,{\cos ^3}\alpha = \frac{{3\sin \alpha - \sin 3\alpha }}{4} \cdot \frac{{3\cos \alpha + \cos 3\alpha }}{4} = \frac{{9\sin \alpha \cos \alpha - 3\cos \alpha \sin 3\alpha + 3\sin \alpha \cos 3\alpha - \sin 3\alpha \cos 3\alpha }}{{16}}.\]

Now we apply the double angle formula for sine

\[\sin 2\alpha = 2\sin \alpha \cos \alpha .\]

Hence

\[\sin \alpha \cos \alpha = \frac{{\sin 2\alpha }}{2},\;\sin 3\alpha \cos 3\alpha = \frac{{\sin 6\alpha }}{2}.\]

By the sine subtraction formula,

\[\sin \alpha \cos 3\alpha - \cos \alpha \sin 3\alpha = \sin \left( {\alpha - 3\alpha } \right) = \sin \left( { - 2\alpha } \right) = - \sin 2\alpha .\]

Then

\[{\sin ^3}\alpha\,{\cos ^3}\alpha = \frac{{\frac{{9\sin 2\alpha }}{2} + 3\left( { - \sin 2\alpha } \right) - \frac{{\sin 6\alpha }}{2}}}{{16}} = \frac{{9\sin 2\alpha - 6\sin 2\alpha - \sin 6\alpha }}{{32}} = \frac{{3\sin 2\alpha - \sin 6\alpha }}{{32}}.\]
Page 1 Page 2